Food deserts? Healthy food access in Amsterdam. (June 2017) - Helbich, Marco; Schadenberg, Björn; Hagenauer, Julian; Poelman, Maartje
Abstract: Healthy food environments are imperative for public health. Access to supermarkets that offer wholesome food products at low prices varies across space and over socioeconomic status and ethnic neighborhoods. This research examined food inequalities in Amsterdam, the Netherlands. Supermarket accessibility was calculated and linked to property prices and the share of native Dutch people on a geographic micro-scale with a spatial resolution of 100 meters. Mann–Whitney tests and Spearman correlations were used to test differences and associations between accessibility, property prices, and the share of natives per area. The spatially explicit contextual neural gas approach was used for data clustering. The results show access differences in supermarkets in favor of areas with high property prices and those areas with a large share of native Dutch people. The correlations indicate that low-priced areas and those with a low share of native Dutch people have a lower supermarket density, but the results are the opposite when proximity to and variety of supermarkets are examined. The clustering revealed no evidence of undersupplied areas. Pronounced inequalities in access to healthy food could not be confirmed. On the basis of this analysis, there is no urgent need for policymakers to intervene in the geographies of supermarkets. Highlights: Accessibility to healthy food (i.e., supermarkets) is important for public health. Undersupplied areas in Amsterdam (NL) were searched for using a spatial clustering approach. No clear evidence was found for the existence of undersupplied areas. The results do not call for policy interventions in the geographies of supermarkets.